2007
DOI: 10.1177/0193945907302729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Inpatient Nurse-Directed Smoking Cessation Program

Abstract: The purpose of this study was to evaluate the effect of a nurse-directed smoking cessation intervention for adults hospitalized in a small community hospital using a quasiexperimental, prospective, longitudinal design with biochemical validation of self-reported tobacco abstinence. Sixty-eight inpatients were assigned to either a control (n = 30) or an intervention group (n = 38). The control group received smoking cessation literature. The intervention group received smoking cessation literature and a nursing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…; Taylor et al. ), content review as video file (Gies ; Johnson et al. ; Quist‐paulsen & Gallefoss ; Ratner et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Taylor et al. ), content review as video file (Gies ; Johnson et al. ; Quist‐paulsen & Gallefoss ; Ratner et al.…”
Section: Resultsmentioning
confidence: 99%
“…) and in the hospital (Canga et al. ; Gies ; Quist‐paulsen & Gallefoss ; Simon et al. ; Smith et al.…”
Section: Resultsmentioning
confidence: 99%
“…In a search of the literature, nursing diagnoses pertinent for the HF population were decreased cardiac output, ineffective breathing pattern, impaired gas exchange (Gardetto & Carroll, 2007), deficient knowledge (Harrison, Graham, Logan, Toman, & Friederg, 2007), excess fluid volume, disturbed sleep pattern (Assis & Barros, 2003), low self‐esteem, fatigue, social isolation (Stanley, 1999), activity intolerance (Assis & Barros, 2003; Stanley, 1999), hopelessness (Roberts, Johnson, & Keely, 1999), and anxiety (Scott, Setter‐Kline, & Britton, 2004). Identified nursing interventions were teaching: individual and teaching: family (e.g., diet, exercise, medication, symptom relief, disease process) (Gardetto & Carroll, 2007; Jaarsma et al., 2000; Stanley, 1999), reminiscence therapy, exercise promotion, spiritual support, hope instillation, family involvement promotion, active listening, advocacy/health system guidance, mutual goal setting (Roberts et al., 1999), weight management, assisting with end‐of‐life decisions/decision‐making support (Stanley, 1999), behavior management (Gardetto & Carroll, 2007), smoking/tobacco cessation assistance (Gardetto & Carroll, 2007; Gies, Buchman, Robinson, & Smolen, 2008), oral health promotion (O'Connor, 2008), and discharge planning (Gardetto & Carroll, 2007; Phillips et al., 2004). Patient outcomes reported as important to the HF population were cardiac pump effectiveness (Lee et al., 2004), symptom severity (Stanley, 1999), self‐care status (Gardetto & Carroll, 2007; Jaarsma et al., 2000), and quality of life (Gardetto & Carroll, 2007; Scott et al., 2004; Stanley, 1999).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Interventions to improve smoking cessation services are effective in significantly improving nurse self‐report of the implementation of smoking cessation services and patient report of satisfaction with services (Duffy, Reeves, Hermann, Karvonen, & Smith, 2008; Essenmacher, Karvonen‐Gutierrez, Lynch‐Sauer, & Duffy, 2009). Active intervention studies are in progress worldwide (Zwar et al, 2010), and many have already demonstrated effectiveness in reducing smoking (Gies, Buchman, Robinson, & Smolen, 2008; Smith & Burgess, 2009; Wewers, Ferketich, Harness, & Paskett, 2009).…”
mentioning
confidence: 99%